Molecular Response Assessment with Immune Adaptive PERCIST in Lung Cancer Patients Treated with Nivolumab: Is It Better Than iRECIST? - Gupta, Manoj; Choudhury, Partha S.; Jain, Parveen; Sharma, Manish; Koyyala, Venkata P. B.; Goyal, Sumit; Agarwal, Chaturbhuj; Jajodia, Ankush; Pasricha, Sunil; Sharma, Anurag; Batra, Ullas (World Journal of Nuclear Medicine, 2022)
Aims We compared the immune response evaluation criteria in solid tumors (iRECIST) with immune adaptive positron emission tomography response criteria in solid tumors (imPERCIST) in lung cancer patients treated with nivolumab.Materials and Methods Twenty lung cancer patients underwent fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) scan at baseline (PET-0), after four cycles (PET-1) and six to eight cycles (PET-2) of nivolumab were included. Kappa coefficient (k) was derived to see the level of agreement in two response criteria. Progression-free survival (PFS) curves were computed by the Kaplan–Meier method and compared with the Log Rank test. Univariate and multivariate regression for the percentage change in the sum of diameters (SoD), standard uptake value maximum (SUVmax), sum of metabolic tumor volume (SoMTV), and sum of total lesion glycolysis (SoTLG) was computed. A p-value less than 0.05 was considered significant.Results Kappa coefficient showed a substantial level of agreement (k 0.769) in two response criteria. Mean PFS in partial response, stable disease, and progressive disease (PD) patients in iRECIST and imPERCIST was 27.3, 17.7, 4.2, and 23.3, 18.8, 3.8 months, respectively. The Kaplan–Meier method with the log rank test showed a significant difference in PFS on intracomparison within both criteria; however, it was not significant on intercomparison. On univariate analysis, the percentage change in SoD, SoMTV, SoTLG was significant. However, on multivariate analysis, only percentage change in SoD was a significant predictor.Conclusions We concluded that imPERCIST was equally effective as currently recommended criteria iRECIST for response evaluation of nivolumab in lung cancer patients.
Keywords: immune checkpoint inhibitors; nivolumab; lung carcinoma; iRECIST; imPERCIST; progression-free survival